Examining the Impact of COVID-19 Experiences on Reported Psychological Burden Increase in Older Persons: The Effects of Illness Severity and Social Proximity - Heidinger, Theresa; Richter, Lukas (Frontiers in Psychology, 2022)
Previous findings have provided indications that experience of COVID-19 illness of self and other affect mental health unfavorably. However, prior studies do not satisfactorily differentiate according to severity of Covid-19 illness or social proximity, which are both hypothesized to be relevant factors for increased psychological burden. This study provides an in-depth examination of the impact of Covid-19 experience of self and other on mental health, considering illness severity as well as proximity to the infected person (self, close and distant network). It used data on an older population (50+ years) from 28 European countries (n > 40 000 persons) surveyed in summer of 2021 using the Survey of Health and Retirement in Europe (SHARE). Aside from bivariate analyses, a logistic regression model was computed to test the effects of illness severity by personal proximity over and above other stressors of life in the pandemic. Severity of illness was shown to be a contributor to psychological burden increase with the strongest effects among persons who reported own illness experiences or experiences in the close network. Regression analysis confirmed the impact of severe Covid-19 experience in self, close and distant relations. Moreover, even a less severe course impacted burden unfavorably when experienced in the own person and more distant relations. These results prove troubling. Psychological burden is impacted by infection, with experiences in self or close persons being strongest, while even ‘lighter’ experiences in the distant network also have an unfavorable effect, emphasizing the need to gain control of the present pandemic.